Protein kinase C activation causes neurite retraction via cyclinD1 and p60-katanin increase in rat hippocampal neurons - YÜKSEL, MERAL (WILEY, 2013)
Neurons are differentiated postmitotic cells residing in G0 phase of the cell cycle and are unable to proceed through G1 phase, in which cyclinD1 needs to be up-regulated for initiation. Yet, a growing body of evidence has shown that cell cycle re-activation via cyclinD1 up-regulation drives neurons into apoptosis. By contrast, there is also evidence demonstrating cell cycle proteins playing roles in neuronal differentiation. cyclinD1 has been shown to be differently regulated by protein kinase C alpha (PKC-) in various mitotic cells. Based on these different effects, we investigated the role of PKC- on cyclinD1 regulation in hippocampal neurons. Neurons were treated with PKC activator, PMA, and analysed for subcellular distributions of PKC- and cyclinD1. Remarkably, PMA treatment increased nuclear PKC- and cyclinD1, but not PKC-epsilon in hippocampal neurons. Increases in nuclear PKC- and cyclinD1 were accompanied by microtubule re-organisation via increases in tau and retinoblastoma protein phosphorylation levels. Increased p60-katanin and p53 changed the neuronal morphology into neurons with shorter, but increased number of side branches. Since up-regulation of cell cycle is associated with apoptosis in neurons, we also analysed changes in Bax, Bcl-2 early and PARP (poly(ADP-ribose)polymerase), caspase3 late apoptotic markers. However, we did not observe any indication of apoptosis. These data suggest that in addition to their previously known roles in mitotic cells on cell cycle regulation, PKC- and cyclinD1 seem to be important for differentiation, and nuclear PKC- and cyclinD1 interfere with differentiation by promoting microtubule re-organisation through PKC signaling without triggering apoptosis.
Keywords: cell cycle; cyclinD1; neuronal differentiation; p60-katanin; PKC-; CELL-CYCLE PROGRESSION; NEURAL DIFFERENTIATION; D2 CYCLIN; IN-VIVO; MICROTUBULES; EXPRESSION; KATANIN; D1; PHOSPHORYLATION; DISEASE